Erythema nodosum and reactive arthritis accompanying tuberculosis: A case report (Indian Journal of Case Reports, 2018)
Erythema nodosum (EN) is the most common panniculitis, appearing as crops of erythematous nodules located symmetrically on the anterior aspect of lower extremities. It is precipitated by several infectious and non-infectious causes with primary tuberculosis (TB) being its most common cause in developing countries. Reactive arthritis associated with TB is known as